Nivel de conocimiento sobre el aborto y su impacto biopsicosocial en adolescentes estudiantes del 9no y 10mo año de Educación Básica del Colegio Nacional Técnico Pasaje de la ciudad de Pasaje periodo 2012-2013. - Carrión Zari, Jéssica Paola (2012)
This research focuses on the level of knowledge about abortion and its biopsychosocial impact on adolescents 9th and 10th year of Basic Education Technical College Pasaje context problem that arises in the educational process, for which we proceeded to research taking into account to the extent that work in education would improve the level of knowledge in students.